Respostas
respondido por:
1
Primeiro passo resolvemos as operações:
![(1-2i)-(1+i)(2-2i)\\(1-2i)-(2-2i+2i-2i^2)\\(1-2i)-(2-2i^2)\\(1-2i)-(2-2(-1))\\
(1-2i)-(2+2)\\(1-2i)-4\\1-2i-4=-3-2i (1-2i)-(1+i)(2-2i)\\(1-2i)-(2-2i+2i-2i^2)\\(1-2i)-(2-2i^2)\\(1-2i)-(2-2(-1))\\
(1-2i)-(2+2)\\(1-2i)-4\\1-2i-4=-3-2i](https://tex.z-dn.net/?f=%281-2i%29-%281%2Bi%29%282-2i%29%5C%5C%281-2i%29-%282-2i%2B2i-2i%5E2%29%5C%5C%281-2i%29-%282-2i%5E2%29%5C%5C%281-2i%29-%282-2%28-1%29%29%5C%5C%0A%281-2i%29-%282%2B2%29%5C%5C%281-2i%29-4%5C%5C1-2i-4%3D-3-2i)
Temos o novo número complexo:
seu conjugado será: ![z'=-3+2i z'=-3+2i](https://tex.z-dn.net/?f=z%27%3D-3%2B2i)
Espero ter ajudado :)
Temos o novo número complexo:
Espero ter ajudado :)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás